(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The current research focuses on assessing the effectiveness of medical herbs in the preparation of topical gels to manage skin ailments. Further, for the plant selection, the roots of Rubia cordifolia were taken since they were known to be effective in treating ailments. The roots were authenticated, shade dried and then extracted using ethanol. The obtained extracts were further used in gel formulations through various polymers such as Carbopol 934, HPMC K4, and HPMC K15. These gels were subjected to checks on their stability, cohesiveness and their pH level and phytochemical potentials. Some of the increases chemical compounds known to be useful including alkaloids, flavonoids, anthraquinones, glycosides, tannins steroids, phenol, and saponin were further confirmed through other tests. This work highlights that in accomplishing our research objectives, Rubia cordifolia root extracts show great promises in the formulation of topical antidermatophytic agents, thus aspiring to advance the knowledge of herbal medicine therapeutics.